5-flourouracil vs. beta-aiiadiation in the prevention of pterygium recurrence (2004)
Aim: The aim of this study was to compare 5-fluorouracil (5-FU) with beta-irradiation in the prevention of pterygium recurrence. Materials and methods: A retrospective non-randomised review of cases of fleshy pterygium treated with bare sclera excision and adjuvant 5-FU were compared with similar morphologically appearing ptervgia, marched for age and sex, treated with bare seleral excision and adjuvant beta-irradiation. All surgeries were carried out at the university college hospital and Ojulowo eye hospital, Ibadan, Nigeria. Results: Twenty-seven eyes of 24 patients who had pterygium excision with adjuvant treatment with 5-FU were compared with 31 eyes of 24 patients who were treated with excision and beta-irradiation. The mean age for the 5-FU group was 46.1 years while that for the beta-irradiation group was 46.9 years. Both sexes were equally represented, 12 males and 12 females. There were seven (25.9%) initial recurrences in the 5-FU group but four of these became atrophic, and therefore, cosmetically acceptable leaving three eyes (11 %) with unacceptable recurrent pterygium. The beta-irradiation group, however, had seven (22.5) initial recurrence but five of these became atrophic and fell short of the cornea, leaving two (6.5%) with clinically unacceptable recurrence. The difference was, however, nor statistically significant (Zc = 0.74 and p > 0.1). The associated complications were mostly mild in both groups and included cornea opacitv of 10 (37%) complications, conjunctivitis of three (11 %) complications, sclera granuloma of three (11%) complications and conjunctiva necrosis of one (3.7%) complication for the 5-FU group, and while the beta-irradiation group had corneal opacity of one(3.7%) complication and conjunctivitis of three (11%) complications. Conclusion: The non-statistical significance of a lower pterygium recurrence rate with use of beta-irradiation for the treatment of fleshy pterygium compared with 5-FU may have been partly due to the small number of patients studied. A randomised-controlled study using a larger sample size is therefore proposed. However, the fact that over half of those with initial recurrence in the 5-FU group became atrophic (and therefore cosmetically acceptable) over rime as well as less cost implication in the purchase of 5-FU relative to Strontium-90 association with few and mild complications makes it a desirable adjuvant therapy in depressed economics. However, beta-irradiation still has a place when cost issue is not an inhibiting factor in view of its clinically superior outcome